A study of organization, challenges & importance of corporate memory in the co-working space business industry in Malaysia - Azmi, Noraishah Intau; Mohd Shoid, Mohd Shamsul; Pati Khan, Mazlina (Faculty of Information Management, 2025)
This study explores the organizational background, challenges, and the critical importance of corporate memory within the co-working space industry in Malaysia. The study highlights the main challenges to continuity and innovation in a market that is changing quickly by looking at how institutional memory and common knowledge affect business operations. The results highlight the importance of corporate memory and the necessity for effective knowledge management techniques to improve competitive advantage and long-term viability in the co-working space industry.